Zakat as a Media for Poverty Alleviation - Mahlel Mansur (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
The problem of poverty and income inequality is still the main enemy of this country. This shows that modern theory which says that economic growth will be able to solve the problem of poverty and create an equal distribution of income through the trickle-down effect scheme is no longer relevant, especially in developing countries, including Indonesia. In Islam, poverty is something that is dangerous for humans because it can damage faith, morals, thoughts, and families. So in this case in Islam poverty must get a solution through fiscal policy, namely in the form of zakat. This research uses the method of library research (library research) using a descriptive analysis approach. Data analysis techniques used are editing, organizing (grouping data), and finding. The results of the study show that the role of Zakat in alleviating poverty is the awareness of the aghniya' to pay zakat and issue sadaqah. If all rich people in various Islamic countries want to pay their zakat proportionally and distribute it fairly and eradicate poverty, it will surely disappear.